Problem-based learning in improving critical mathematical thinking skills: Independent curriculum teaching module - Juniati, Helmira; Jamaan, Elita Zusti (Universitas Islam Raden Intan Lampung, INDONESIA, 2024)
Background: Students' limited abilities in critical mathematical thinking present a persistent obstacle in mathematics education. To address this issue, this study focuses on developing a teaching module aligned with the Independent Curriculum, incorporating the Problem-Based Learning (PBL) approach.Aim: This research aims to design and validate a teaching module tailored to enhance students' critical thinking skills in solving mathematical problems.Method: Employing the Plomp development model, the study was conducted through three phases: preliminary analysis, development or prototyping, and evaluation. Data collection involved expert validation, with analysis performed using a validity index.Result: The independent curriculum teaching module received an average validity score of 3.57, categorized as highly valid, confirming its feasibility and alignment with instructional criteria.Conclusion: The findings demonstrate that the developed module fulfills all validity criteria, making it suitable for use in mathematics education to support the development of critical thinking skills. Further studies are encouraged to investigate its influence on students' learning outcomes.